Effects of Feeding Frequency for Nile Tilapia Fingerlings (Oreochromis niloticus) - Aldo Felipe Fava; Gildete de Souza Bezerra; Dacley Hertes Neu; Fabio Bittencourt; Altevir Signor; Kerolay Valadão Carvalho; Ricacio Luan Marques Gomes; Wilson Rogério Boscolo (Aquaculture Nutrition)
This study is aimed at assessing the feeding frequency for tilapia fingerlings. 240 fishes were randomly distributed in 24 containers. The feeding consisted of six frequencies: 4 (F4), 5 (F5), 6 (F6), 7 (F7), 8 (F8), and 9 (F9) times a day. The weight gain was significantly higher in F5 and F6 when compared to F4 (p=0.0409 and 0.0306, respectively). Feed intake and apparent feed conversion did not differ between treatments (p=0.129 and p=0.451). About water quality, the nitrogen levels in the water from the treatments differed between F4 and F5 (p=0.0478) and F4 and F6 (p=0.0283) and for P between F4 and F6 (p=0.0215) and F4 and F9 (p=0.0432). The x2 test showed a dependence relationship between feed frequencies and the muscle fibers frequency (p<22×10−17), prevailing fibers between 10-20 micrometers in F4, F5, F6, and F7 and 30-40 in F8 and F9. The area of the hepatocytes differed only between F5 and F9, while the nucleus area did not. Partial net revenue differed in 10% between F5 and F4 (p=0.0812) and between F6 and F4 (p=0.0568). In conclusion, fingerlings fed 5 to 6 times a day have better zootechnical and partial recipes.